ADVERSE EVENTS FOLLOWING IMMUNIZATION OF THE ELDERLY - Lúcia Helena Linheira-Bisetto; Suely Itsuko Ciosak; Thaís Lazaroto Roberto Cordeiro; Muriel de Souza Boing (Universidade Federal do Paraná, 2016)
The aim of this study was to analyze the occurrence of adverse events following immunization of the elderly, in Brazil, from 2004 to 2013. This is a descriptive, retrospective, quantitative study with data from the National Information System on Adverse Events Following Immunization, related to vaccines against diphtheria and tetanus, hepatitis B, pneumococcal 23-valent, yellow fever and influenza, in Brazil, collected in April 2015. Data were analyzed with descriptive statistics using Microsoft Excel 2013® and Epi Info® 7.1.4. A total of 2,692 adverse events were found, 97.91% were not severe. Of these, 37.11% involved pain, heat and flushing, prevalent in influenza (42.64%) and diphtheria, and tetanus (39.64%) vaccines. The elderly from 60-69 years (71.65%) and females (76.19%) were the most affected. Of the cases, 59.32% did not receive care in health services. It was concluded that this population is affected by adverse events, especially with no severity, but that require the attention from healthcare professionals to maintain their trust and adherence to vaccination.